Impact of Covid-19 on Financial Ratio Banking Sector - Nadiyah Rahmani, Annisa; Suangga, Asri; ., Lasmanah; Pradiftha Drajat, Radhitya; Permatasari, Tasya (KnE Social Sciences, 2023)
The purpose of this research is to provide information on whether the COVID-19 pandemic had an impact on banking in Indonesia, especially for banks listed on the Indonesia Stock Exchange. The impact on banking was measured by using financial performance ratios, namely nonperforming loan (NPL), operating expenses to operating income (BOPO), net interest margin (NIM), and liquidity coverage ratio (LCR). Researchers used comparative data on financial statements, namely in 2019 and 2020. The tool used by researchers to process research data was SPSS 24. Researchers used different test methods to determine the impact of the Covid-19 pandemic on the financial performance of the banking sector. The results showed that the Covid-19 pandemic had affected the financial performance of the banking sector. Keywords: financial performance, Covid-19, banking sector